Gata3/Ruvbl2 complex regulates T helper 2 cell proliferation via repression of Cdkn2c expression - Hosokawa, Hiroyuki; Tanaka, Tomoaki; Kato, Miki; Shinoda, Kenta; Tohyama, Hiroyuki; Hanazawa, Asami; Tamaki, Yuuki; Hirahara, Kiyoshi; Yagi, Ryoji; Sakikawa, Ikue; Morita, Atsushi; Nagira, Morio; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
GATA-binding protein 3 (Gata3) controls the differentiation of naive CD4 T cells into T helper 2 (Th2) cells by induction of chromatin remodeling of the Th2 cytokine gene loci, direct transactivation of Il5 and Il13 genes, and inhibition of Ifng . Gata3 also facilitates Th2 cell proliferation via additional mechanisms that are far less well understood. We herein found that Gata3 associates with RuvB-like protein 2 (Ruvbl2) and represses the expression of a CDK inhibitor, cyclin-dependent kinase inhibitor 2c (Cdkn2c) to facilitate the proliferation of Th2 cells. Gata3 directly bound to the Cdkn2c locus in an Ruvbl2-dependent manner. The defect in the proliferation of Gata3 -deficient Th2 cells is rescued by the knockdown of Cdkn2c , indicating that Cdkn2c is a key molecule involved in the Gata3-mediated induction of Th2 cell proliferation. Ruvbl2-knockdown Th2 cells showed decreased antigen-induced expansion and caused less airway inflammation in vivo. We therefore have identified a functional Gata3/Ruvbl2 complex that regulates the proliferation of differentiating Th2 cells through the repression of a CDK inhibitor, Cdkn2c .